Floral visitors of three species of Corallorhiza in Monte Tláloc, Texcoco, Estado de México, México - Téllez Baños, Bruno Enrique
Corallorhiza is a genus of mycoheterotrophic orchids that includes 12 species, most of them re-stricted to North and Central America. In Mexico, there are seven taxa, distributed throughout the country, except for seven of the 32 Mexican states; in Estado de México all of them are present. The Orchidaceae is known for its diversity of pollination syndromes; however, for the more than 200 species of mycoheterotrophic orchids, little has been studied about their floral visitors and pollinators, and for the Mexican species of Corallorhiza nothing is known to date. Our goal was to document photographically and identify all the floral visitors of three sympatric species of the genus in Monte Tláloc, municipality of Texcoco, Estado de México. We observed individuals of Araneae, Coleoptera, Diptera, Hemiptera, and Hymenoptera visiting flowers of Corallorhiza macrantha, C. macrantha × C. maculata, C. maculata, and C. striata. Only Ocyptamus coeru-leus and Platycheirus sp. (Diptera: Syrphidae) were found carrying pollinaria on their thorax. These are the first records of potential pollinators for the genus Corallorhiza in Mexico.